Drivers of Financial Performance in Urban Art Markets: Access to Capital and the Isolation of Internal Entrepreneurial Assets - Edi Wibowo; Setyaningsih Sri Utami; Sumaryanto Sumaryanto (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This research investigates the drivers of financial performance among Micro, Small, and Medium Enterprises (MSMEs) in creative tourism districts. Specifically, it evaluates access to capital and network collaboration as direct predictors of financial performance, while examining intellectual capital and entrepreneurial orientation as internal antecedents of network collaboration within a mediation framework. Methodology – A quantitative approach was employed, collecting questionnaire data from MSME operators within the Urban Street Art Market along the Gatsu Corridor in Surakarta, Indonesia. Structural Equation Modeling via Partial Least Squares (PLS-SEM) was executed for measurement and structural model evaluations. Finding/Results – The results reveal that MSME financial performance is primarily driven by access to capital (β = 0.430, t = 5.650, p < 0.001) and network collaboration (β = 0.335, t = 3.599, p < 0.001). Conversely, intellectual capital and entrepreneurial orientation do not significantly affect network collaboration, leading to the rejection of all mediation hypotheses. The framework explains a moderate portion of financial performance (R² = 0.408) but is weak in predicting network formation (R² = 0.092). Originality/Value – This research highlights a unique empirical gap in creative art clusters: internal intellectual or entrepreneurial assets do not automatically foster external cooperation. Within informal creative spaces, collaborative networks behave as passive structures, implying that structural success depends more on systemic capital accessibility and external institutional support than on individual capacity building alone